TWO TURBULENT DECADES IN THE NEW MILLENNIUM : TO WHAT EXTENT WAS A ‘CLASH OF CIVILIZATIONS’ INEVITABLE ? - Mahfoud ALI ZOUI & Asma FRIHI (Ziglôbitha)
Abstract : The grand turbulences that have shaped the world during the first two decades of the new millennium triggered a renewed debate over the validity of the predictions of the controversial ‘clash of civilizations’ thesis. The mounting friction between the West and forces within the Islamic world since the launching of the post-9/11 US-led Global War on Terror prompted many scholars to revisit Huntington’s paradigm with some arguing that the events are a testimony to the validity of its propositions. Contextualizing the post-9/11 events and highlighting the fallacies of the inevitability of the clash of civilizations paradigm, this paper argues that the major clashes that have taken place during the first 20 years in the new millennium do not provide any support to the claim that major world civilizations, namely those of Islam and the West, are destined to clash. Keywords: clash of civilizations,9/11,the New Millennium,Huntington ,the Global War on Terror.